2001
DOI: 10.1016/s0040-6031(01)00478-6
|View full text |Cite
|
Sign up to set email alerts
|

Bitumen microstructure by modulated differential scanning calorimetry

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
138
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(147 citation statements)
references
References 25 publications
8
138
0
1
Order By: Relevance
“…With bitumen, the two phases are the maltenes and the asphaltenes, and what the MDSC non-reversing heat flow effectively shows (Figure 2) is the rate at which the asphaltenes segregate out of the maltenic phase to form the asphaltenic mesophase. 6 Given the isotropization of the mesophase at 40-50°C and the steric hardening below 60°C, 3 a UCST is likely close to 60°C. It would be below this UCST that asphaltenes would order into a mesophase, possibly due to nucleation and growth, 11 and that steric hardening would arise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With bitumen, the two phases are the maltenes and the asphaltenes, and what the MDSC non-reversing heat flow effectively shows (Figure 2) is the rate at which the asphaltenes segregate out of the maltenic phase to form the asphaltenic mesophase. 6 Given the isotropization of the mesophase at 40-50°C and the steric hardening below 60°C, 3 a UCST is likely close to 60°C. It would be below this UCST that asphaltenes would order into a mesophase, possibly due to nucleation and growth, 11 and that steric hardening would arise.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 The segregation being time dependent, it was suggested that the formation of the mesophase was responsible for the steric hardening of bitumen. This communication provides evidence of this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, above the frozen state defined by T > Tg, molecular mobility increases and those saturates segments order into crystalline domains [22,23,25]. Table 2, which displays second event temperatures (T2nd) confirms a decrease after addition of 9 wt.% Th and 60 days of curing, as the frozen state threshold was shifted to lower temperatures.…”
Section: On the Chemistry Behind Bitumen Modification Via Thioureamentioning
confidence: 67%
“…8B presents two welldefined peaks (with peak maximum, Tg1 and Tg2, located at -30.5 and 3.0 ºC, respectively) which, according to Masson et al [22,23], derive from two overlapped glass transitions corresponding to saturates and aromatics. Tg2 values were also determined for the modified binders studied, and compare with neat bitumen's.…”
Section: On the Chemistry Behind Bitumen Modification Via Thioureamentioning
confidence: 88%
See 1 more Smart Citation